Environmental factors associated with allergic rhinitis symptoms in Japanese university students: A cross-sectional study. Issue 5 (October 2018) - Nishijima, Hironobu; Suzuki, Sayaka; Kondo, Kenji; Yamasoba, Tatsuya; Yanagimoto, Shintaro
Abstract: Objective: Numerous studies have reported that various environmental factors during early life are key determinants for developing allergic disease. Herein, we aimed to investigate the impact of environmental factors on allergic rhinitis. Methods: This cross-sectional study was conducted in a single university in Japan (from April to June, in 2015 and 2016). Students voluntarily answered online questionnaires regarding their allergic rhinitis symptoms and their exposure to various environmental factors during preschool-age. Results: Overall, 3075 students participated the questionnaire. After excluding those with incomplete datasets, 3016 students were eligible. Of these, 49% had allergic rhinitis symptoms. Female sex was associated with a lower risk of allergic rhinitis symptoms (odds ratio [OR], 0.82; 95% confidence interval [CI], 0.68–0.99). Comorbidity of asthma or atopic dermatitis and a family history of allergy (asthma, atopic dermatitis, or allergic rhinitis) were associated with higher risks of allergic rhinitis symptoms. Regarding the number of household members, compared with subjects with <3 people, those with 5 (OR, 0.74; 95% CI, 0.57–0.97) and ≥6 people (OR, 0.66; 95% CI, 0.49–0.88) in their household showed lower incidences of allergic rhinitis symptoms. No other environmental factors, including birth order, number of siblings, living environment, passive smoking, furry pet ownership, housing, bedding, breastfeeding, dairy product intake, preschool setting, and starting age of preschool, was associated with the incidence of allergic rhinitis symptoms. Conclusion: Sex, current asthma and atopic dermatitis symptoms, family history of allergies, and the number of people in the household at preschool-age were associated with the incidence of allergic rhinitis symptoms.